The quality of society and happiness: fairness, trust, and community in China - Knight, J; Gunatilaka, R (University of Oxford, 2023)
Adam Smith argued that ‘moral sentiments’ – the norms, customs and conventions that are developed in society - provide a benefit to society, improving both economic efficiency and well-being. We take our cue from this insight. Three important moral sentiments are a perception of fairness, a willingness to trust people, and a sense of community We analyse representative national socioeconomic surveys of the China Household Income Project (CHIP), conducted in 2002 and 2013. It contains information that is used to create a happiness score, a fairness score, a trust score, and a community score for each respondent.